هابرماس في نقد العقل الأداتي من ماكس فيبر إلى هوركهايمر وأدورنو - محمد, منيرة; محمد, سحر (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
Through the examination of several critics of instrumental reason, this study seeks to determine the ability of one of them to look after and through the complexity of modern Western society. First, the problem willbe introduced with reading Max Weber as it is proposed by Jûrgen Habermas. It will be a matter of Weber's phenomenon of rationalization of society. Based on the evidence that cognitive-instrumental sphere of reason is strongly needed in modernity that it will be explained by reflecting on the historical process of the "disenchantment of the world" and how the rationality report to an end as it was able to become so dominant. Subsequently, it will present the criticism of the reification in modern societies as it was contributed bythe Marxist PhilosopherGeorg Lukács and will examine the Critical theory of Max Horkheimer and Theodor W. It will also examine Adorno on the instrumental reason as it was shaped historically, and then will show that the reason is totalitarian in its essence; reason has always produced the domination and violence in all its relations; the nature, society and subjectivity. From the very first step of man, up to Enlightenment through myth, reason has always been totalitarian. Finally, Habermas proposes a paradigm shift that he believes is necessary to overcome theconcept of reason reduced to a single cognitive-instrumental potential. It is in the paradigm language where Habermas found the missing link to enter therich potential of communicative rationality. Then,by this new paradigm, he could adequately conceptualize the two levels that make up modern societ; system and living.تسعى هذه المقالة إلى تتبّع أشكال ونماذج نقدية اهتمّت بتطوّر العقلانية الحداثية في الغرب، وأخذت على عاتقها تبيّن المسار الضار والأداتي للعقل وانحرافه عن أهدافه الأولى مع انبثاق الحداثة في الغرب في القرن السادس عشر. نقترح في هذه الدراسة تتبع ثلاثة مسارات فكرية أو نماذج إيديولوجية ومعرفية بآن، كما تبيّنها الفيلسوف الألماني يورغين هابرماس Jûrgen Habermas في عمله الضخم "نظرية الفعل التواصلي"، ألا وهي قراءة فكر ماكس فيبر Max Weberحول نقد الحداثة، عبر التشديد على مفهوم "نزع السحر عن العالم" لديه وتبيّن مفاصله الأساسية، وكيف يمكن للعقلانية أن تتشكّل وفق غاية محددة وأن تتحوّل بهذا إلى قوّة مهيمنة على المؤسسات الإجتماعية؟ ثمّ نتوقف مع المساهمة النقدية الماركسية التي تقدمّ بها جورج لوكاتش Georg Lukács عبر مفهوم التشيّؤ ونقد الصنمية السلعية للثقافة والإنسان، وهي أحد مآلات العقلانية الأداتية. ثمّ نأتي على نقد ماكس هوركهايمر Max Horkheimer وثيودر أدورنو Theodore Adorno للجوهر التنويري للعقل الآداتي ونتتبّع أصوله الأسطورية لدى الإغريق، لنبيّن أنّ العقل بحسب قراءتهما هو عقلٌ مهيمن منذ نشأته الأولى وميّال بحكم جوهره وتاريخه إلى العنف والقهر والشمولية. ونختتم بالنقد الذي وجّهه هابرماس إلى هذه القراءات واعتبرها جزئية ومختزلة في تصوّرها للعقل إلى بعده الإدراكي- الآداتي، وبذك يقترح هابرماس للخروج من هذا المأزق الإنتقال إلى براديغم (نموذج) مغاير هو براديغم اللّغة الذي بحسبه يمكن بناء نظرية في الفعل التواصلي تقوم عليها المجتمعات الحديثة على مستويين اثنين هما: النسق والمعيش.